Interferons as Essential Modulators of Atherosclerosis. Issue 7 (July 2015) - Boshuizen, Marieke C.S.; de Winther, Menno P.J.
Abstract : Interferons (IFNs) are key regulators of both innate and adaptive immune responses. The family of IFN cytokines can be divided into 3 main subtypes of which type I and type II IFNs are most well-defined. IFNs are known to be important mediators in atherosclerosis. Evidence from both in vitro and in vivo studies shows that the IFNs are generally proatherosclerotic. However, their role in atherosclerosis is complex, with distinct roles for these cytokines throughout different stages of the disease. In this review, we will discuss the current knowledge on the role of type I and type II IFNs in atherosclerosis development, specifically focusing on their role in endothelial activation, cell recruitment, foam cell formation, and regulation of apoptosis. Furthermore, we will discuss whether IFNs could be considered as new molecular targets for therapeutic intervention in atherosclerosis.